Universality of energy-momentum response in kinetic theories - Du, Xiaojian; Ochsenfeld, Stephan; Schlichting, Sören (arXiv:2306.09094)
We study the response of the energy-momentum tensor in several kinetic theories, from the simple relaxation time approximation (RTA) to Quantum Chromodynamics (QCD). Irrespective of the differences in microscopic properties, we find a remarkable degree of universality in the response functions from conformal theories. We find that the response to scalar perturbations in kinetic theory can be effectively described by a pair of one hydrodynamic sound mode and one non-hydrodynamic mode. We find that even beyond the range of validity of hydrodynamics, the energy-momentum response in position space can be effectively described by one single mode with non-trivial dispersion relation and residue.

Optogenetics reveals paradoxical network stabilizations in hippocampal CA1 and CA3 - de Jong, Laurel Watkins; Nejad, Mohammadreza Mohagheghi; Yoon, Euisik; Cheng, Sen; Diba, Kamran (Current Biology)

Investigation of the Compatibility between Warheads and Peptidomimetic Sequences of Protease Inhibitors—A Comprehensive Reactivity and Selectivity Study - Müller, Patrick; Meta, Mergim; Meidner, Jan Laurenz; Schwickert, Marvin; Meyr, Jessica; Schwickert, Kevin; Kersten, Christian; Zimmer, Collin; Hammerschmidt, Stefan Josef; Frey, Ariane; Lahu, Albin; de la Hoz-Rodríguez, Sergio; et al. (International Journal of Molecular Sciences)
Covalent peptidomimetic protease inhibitors have gained a lot of attention in drug development in recent years. They are designed to covalently bind the catalytically active amino acids through electrophilic groups called warheads. Covalent inhibition has an advantage in terms of pharmacodynamic properties but can also bear toxicity risks due to non-selective off-target protein binding. Therefore, the right combination of a reactive warhead with a well-suited peptidomimetic sequence is of great importance. Herein, the selectivities of well-known warheads combined with peptidomimetic sequences suited for five different proteases were investigated, highlighting the impact of both structure parts (warhead and peptidomimetic sequence) for affinity and selectivity. Molecular docking gave insights into the predicted binding modes of the inhibitors inside the binding pockets of the different enzymes. Moreover, the warheads were investigated by NMR and LC-MS reactivity assays against serine/threonine and cysteine nucleophile models, as well as by quantum mechanics simulations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Apologie für das Nebensächliche. Prinzipien einer intersektional orientierten Unterrichtsmodel-lierung am Beispiel von Aneignungsperspektiven zu einer jugendpopulären Fernsehserie - Kißling, Magdalena (Rassismussensibler Literaturunterricht – Grundlagen, Dimensionen, Herausforderungen, Möglichkeiten)

Differenzkonstruktionen in Explikation und Beiläufigkeit. Vergleichende Betrachtungen zur Wirkungsästhetik bei Fünftklässler:innen hinsichtlich unterschiedlichen kinderliterarischen Erzählens von Diversität - Kißling, Magdalena ("So viel Größenwahn muss sein!" Kinderliteratur - Schule - Gesellschaft)

Diskriminierungssensible Methoden. Neue Lernwege im kulturwissenschaftlich ausgerichteten Literaturunterricht - Kißling, Magdalena (Neue Perspektiven einer kulturwissenschaftlich orientierten Literaturdidaktik)

Hannah Arendt and Politics - Robaszkiewicz, Maria Anna; Weinman, Michael D.

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Le Gall, François (SIAM Journal on Computing)
Keywords: General Mathematics; General Computer Science

Untersuchung der Dichtheitseigenschaften hybridgefügter Mischbauverbindungen für den Einsatz in Batterieghäusen für Elektrofahrzeuge - Schmolke, Tobias; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

Experimentelle Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

Effizientes Lösen von Klebverbindungen in der Fahrzeuginstandsetzung - Chudalla, Nick; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

„Wir fahren jetzt nicht mit’m Mercedes vor, wenn man sich nachher eigentlich nur ‘n Polo leisten kann.“ Vorstellungen von Transfer in Theorie und Praxis der Beruflichen Bildung und ihre Implikationen - Daniel-Söltenfuß, Desiree

Zum Verständnis von Innovation und Transfer in einer vernetzten Berufsbildungspraxis. Ergebnisse einer übergreifenden Interviewstudie - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

Optimizing the Streaming of Sensor Data with Approximate Communication - Sadeghi-Kohan, Somayeh; Reimer, Jan Dennis; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Asian Test Symposium (ATS'23), October 2023)

„Go with the flow?!“ Einblicke in Forschungsansatz und erste Ergebnisse des Begleitforschungsprojekts ITiB - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

Packings and Steiner systems in polar spaces - Schmidt, Kai-Uwe; Weiß, Charlene (Combinatorial Theory)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-Steiner system in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $n$-spaces such that each totally isotropic $t$-space is contained in exactly one member of $Y$. Nontrivial examples are known only for $t=1$ and $t=n-1$. We give an almost complete classification of such $t$-Steiner systems, showing that such objects can only exist in some corner cases. This classification result arises from a more general result on packings in polar spaces.

Existence of small ordered orthogonal arrays - Schmidt, Kai‐Uwe; Weiß, Charlene (Journal of Combinatorial Designs)
We show that there exist ordered orthogonal arrays, whose sizes deviate from the Rao bound by a factor that is polynomial in the parameters of the ordered orthogonal array. The proof is nonconstructive and based on a probabilistic method due to Kuperberg, Lovett and Peled.

Linear programming bounds in classical association schemes - Weiß, Charlene
Digital communications relies heavily on the usage of different types of codes. Prominent codes nowadays are rank-metric codes and subspace codes - the q-analogs of binary codes and binary codes with constant weight. All these codes can be viewed as subsets of classical association schemes. A central coding-theoretic problem is to derive upper bounds for the size of codes. This thesis investigates Delsartes powerful linear program whose optimum is precisely such a bound for codes in association schemes. The linear programs for binary codes and binary constant-weight codes have been extensively studied since the 1970s, but their optimum is still unknown. We determine in a unified way the optimum of the linear program in several ordinary q-analogs as well as in their affine counterparts. In particular, bounds and constructions for codes in polar spaces are established, where the bounds are sharp up to a constant factor in many cases. Moreover, based on these results, an almost complete classification of Steiner systems in polar spaces is provided by showing that they could only exist in some corner cases.

"Fotonotizen". documenta fifteen - Autsch, Sabiene (Impulse 6. Texte und Bilder zur Kunstvermittlung: ABHÄNGEN. Ein interdisziplinäres Projekt zur documenta fifteen (2022))

"More human than human.“ – Biopolitik und Geschlecht in Alex Garlands Ex Machina - Puscher, Sahra (Biopolitik(en) in Literatur, Film und Serie. Aushandlungs- und Reflexionsräume vom 18. Jahrhundert bis heute)